1995
DOI: 10.1007/bf00024481
|View full text |Cite
|
Sign up to set email alerts
|

Mass-marking of bone tissue of Coregonus lavaretus L. and its potential application to monitoring the spatio-temporal distribution of larvae, fry and juveniles of lacustrine fishes

Abstract: Mass labelling techniques have great potential for the study of larval fish dynamics in closed habitats (lakes, ponds and flooded quarries) . Different methods of mass labelling of bone tissue were tested : bathing in tetracycline solutions with or without osmotic shock, and modification of otolith microstria by temperature, photoperiod or feeding manipulations using different batches of eggs, eleuteroembryos, larvae and prefed fry of Coregonus lavaretus L . from Lake Leman . A short period of immersion with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
2
6
0
1
Order By: Relevance
“…Mark retention was verified in this study over at least 8 months, while much longer retention times of fluorescent marks have already been reported (Rojas-Beltran et al 1995a;Unkenholz, Brown & Pope 1997;). Thus, it appears safe to assume that mark retention will not be a problem with ARSmarked otolith primordia of whitefish.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Mark retention was verified in this study over at least 8 months, while much longer retention times of fluorescent marks have already been reported (Rojas-Beltran et al 1995a;Unkenholz, Brown & Pope 1997;). Thus, it appears safe to assume that mark retention will not be a problem with ARSmarked otolith primordia of whitefish.…”
Section: Discussionsupporting
confidence: 83%
“…Earlier studies demonstrated that fish otoliths can be marked with fluorochrome dyes during embryonic development (Dabrowski & Tsukamoto 1986; Tsukamoto 1988; Blom, Nordeide, Svasand & Borge 1994; Nagata et al. 1995; Iglesias & Rodríguez‐Ojea 1997), and that this can be carried out as early as at the time of egg fertilization (Ruhlé & Winecki‐Kuehn 1992; Rojas‐Beltran, Champigneulle & Vincent 1995a). In some of these studies, the transport of the fluorochrome dye across the egg envelope was promoted by osmotic shock (Ruhlé & Winecki‐Kuehn 1992; Rojas‐Beltran et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certaines de ces études ont également démontré que la marque produite reste très bien lisible sur une période allant d'au moins cinq mois à près de deux ans (Blom et al 1994;Beckman et Schulz 1996;Eckmann et al 1998;Eckmann 2003). Tel qu'indiqué par plusieurs auteurs, le marquage des embryons à un stade avancé du développement embryonnaire, équivalent au stade oeillé, permet généralement d'obtenir des résultats convaincants (Tsukamoto 1985;Dabrowski et Tsukamoto 1986;Nagata et al 1995;Rojas-Beltran et al 1995). Les taux de mortalité obtenus ont été également très acceptables, soit de 6 % à 7 % au lac Saint-Jean et de 17 % à 29 % dans le fleuve SaintLaurent.…”
Section: Introductionunclassified
“…Mark retention in red sea bream, Pagrus major (Temminck et Schegel), otoliths, labelled as larvae by immersion in a solution of alizarin complexone, was confirmed 2 years after marking (Tsukamoto et al 1989a). Persistence of otolith marks was achieved for 3 years in glass-eels Anguilla anguilla (L.) (Alcobendas,Lecomte,Castanet,Meunier,Maire & Holll991) and for 2 years in coregonids (Rojas Beltran, Champigneulle & Vincent 1995) by rapid immersion in tetracycline solution with osmotic shock. In all these examples, the marking procedure had no effect on either fish growth or mortality.…”
Section: Introductionmentioning
confidence: 99%